Validation of ozone intensities at 10 µm with THz spectrometry. (December 2017) - Drouin, Brian J.; Crawford, Timothy J.; Yu, Shanshan
Highlights: First characterization of O3 10 µm bandstrength using simultaneous rotational band measurement. Validation of existing linestrengths in HITRAN database. Description of quantitative THz absorption technique. Abstract: This manuscript reports an effort to improve the absolute accuracy of ozone intensities in the 10 µm region via a transfer of the precision of the rotational dipole moment onto the infrared measurement. The approach determines the ozone mixing ratio through alternately measuring seven pure rotation ozone lines from 692 to 779 GHz. A multispectrum fitting technique was employed. The results determine the column with absolute accuracy of 1.5% and the intensities of infrared transitions measured at this accuracy reproduce the recommended values to within a standard deviation of 2.8%.